KAJIAN ANTROPOLOGI SASTRA PADA NASKAH DRAMA “DR. ANDA” KARYA WISRAN HADI - Muhammad Firhan Ariz; Ninda Dawilatul Aliyah; Natasya Marthasifa; Dimas Hermawan; Asma Izzati; Dzikry Aqbil Rais; Adita Widara Putra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
Drama is a literary work that expresses stories about the various portrait of human life through dialogues among it’s characters and is performed as a staging on stage. However sometimes a drama script is not considered as one of the parts of the drama itself, even though if studied fundamentally a drama performance would never succeed without a drama script. In the field of literature, the study of literary becomes an important activity in an effort to uncover and understand the hidden meanings that the author wishes to convey in their literary work. At present, there are various approaches that can be used to study literary work, one of which is the literary anthropology approach. This study to examine in an effort to uncover cultural elements and understand the hidden meanings that Wisran Hadi wants to convey in his drama script titled “Dr. Anda”. This study uses a qualitative method with a hermeneutic approach. In the meantime, the data collection technique using documentation with data analysis techniques using deconstruction. Based on the results of the literary anthropology study, the drama script “Dr. Anda” by Wisran Hadi tells the story of an character named Dr. Anda who delivers a lecture on the culture of the Minangkabau society, particularly the traditional ceremony of the appointment of a penghulu. The author depicts elements of Minangkabau society’s culture, which are rich in meaning and quite philosophical to the readers. Furthermore, this study hopes to provide additional references and relevance to the study of literature in Indonesia, particularly in the study of drama.